Plasma Parathyroid Hormone Is Independently Related to Nocturnal Blood Pressure in Hypertensive Patients: The Styrian Hypertension Study. Issue 6 (12th October 2015) - Verheyen, Nicolas D.; Kienreich, Katharina; Gaksch, Martin; van Ballegooijen, Adriana J.; Grübler, Martin R.; Hartaigh, Briain Ó.; Schmid, Johannes; Fahrleitner‐Pammer, Astrid; Kraigher‐Krainer, Elisabeth; Colantonio, Caterina; Belyavskiy, Evgeny; Treiber, Gerlies; et al.
Abstract : High parathyroid hormone (PTH) has been linked with high blood pressure (BP), but the relationship with 24‐hour ambulatory blood pressure monitoring is largely unknown. The authors therefore analyzed cross‐sectional data of 292 hypertensive patients participating in the Styrian Hypertension Study (mean age, 61±11 years; 53% women). Median plasma PTH (interquartile range) determined after an overnight fast was 49 pg/mL (39–61), mean daytime BP was 131/80±12/9 mm Hg, and mean nocturnal BP was 115/67±14/9 mm Hg. In multivariate regression analyses adjusted for BP and PTH‐modifying parameters, PTH was significantly related to nocturnal systolic and diastolic BP (adjusted β‐coefficient 0.140 [ P =.03] and 0.175 [ P <.01], respectively). PTH was not correlated with daytime BP readings. These data suggest a direct interrelationship between PTH and nocturnal BP regulation. Whether lowering high PTH concentrations reduces the burden of high nocturnal BP remains to be shown in future studies.